2014
DOI: 10.1261/rna.046029.114
|View full text |Cite
|
Sign up to set email alerts
|

The RNA binding domain of Pumilio antagonizes poly-adenosine binding protein and accelerates deadenylation

Abstract: PUF proteins are potent repressors that serve important roles in stem cell maintenance, neurological processes, and embryonic development. These functions are driven by PUF protein recognition of specific binding sites within the 3 ′ untranslated regions of target mRNAs. In this study, we investigated mechanisms of repression by the founding PUF, Drosophila Pumilio, and its human orthologs. Here, we evaluated a previously proposed model wherein the Pumilio RNA binding domain (RBD) binds Argonaute, which in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
119
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(131 citation statements)
references
References 64 publications
12
119
0
Order By: Relevance
“…Second, most FBF binding sites are in the 3 ′ UTR and are enriched toward the terminal end of those UTRs. The bias toward the 3 ′ ends is consistent with the ability of PUF proteins to recruit a deadenylase to the end of target transcripts (Merritt et al 2008;Weidmann et al 2014). Although 3 ′ termini may be more accessible to FBF binding in vivo, major binding site peaks clearly occur across the whole transcript, implying that regions throughout the transcript can mediate PUF control.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Second, most FBF binding sites are in the 3 ′ UTR and are enriched toward the terminal end of those UTRs. The bias toward the 3 ′ ends is consistent with the ability of PUF proteins to recruit a deadenylase to the end of target transcripts (Merritt et al 2008;Weidmann et al 2014). Although 3 ′ termini may be more accessible to FBF binding in vivo, major binding site peaks clearly occur across the whole transcript, implying that regions throughout the transcript can mediate PUF control.…”
Section: Discussionsupporting
confidence: 57%
“…PUF proteins repress their target mRNAs using conserved mechanisms. They can recruit a deadenylase complex, which shortens poly(A)-tail length and destabilizes the transcript (Goldstrohm et al 2006;Suh et al 2009), or they can participate in formation of a ternary complex with an Argonaute protein and translation elongation factor to attenuate translational elongation (Friend et al 2012;Weidmann et al 2014). In addition to their primary role as mRNA repressors, PUF proteins can also activate mRNA expression or localize mRNAs to control expression spatially (Quenault et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent analysis of endogenous Pumilio identified over 600 bound mRNAs and found that these are highly enriched for transcripts that are translationally repressed and degraded during the MZT (Laver et al, 2015). Mechanistically, Pumilio binds POP2 of the CCR4-POP2-NOT-deadenylase complex, accelerates reporter mRNA deadenylation, and antagonizes poly(A) binding protein (PABP) activity (Weidmann et al, 2014). Interestingly, full length Pumilio represses and destabilizes reporter mRNA, while the N-terminal portion predominantly causes repression (Weidmann & Goldstrohm, 2012), suggesting that its role in mRNA destabilization relates to the C-terminal domain’s binding partners or activity.…”
Section: Mechanisms Of Maternal Mrna Clearance During the Mztmentioning
confidence: 99%
“…Ideally, we prefer negative control SEQRS analysis using an RNA-binding defective mutant of the RBP of interest. In the case of Pum, we performed negative control selection using a resin-bound HaloTag fusion of a mutant form of Pum (mutR7) wherein the RNA recognition amino acid residues in the seventh helical repeat were changed to alanine (S1342A N1343A E1346A), thereby preventing RNA binding in vitro and loss of regulation in vivo (42, 43). This control is extremely informative in understanding and assigning significance to binding elements that are weakly enriched.…”
Section: The Methodsmentioning
confidence: 99%
“…For example, the use of reporter assays has facilitated identification of repressive regions outside of the PUF domain and sites of interaction with mechanistically relevant protein partners (18, 42, 43, 52, 53). To facilitate implementation and analysis of reporter genes, we refer readers to our recent methods article, which focuses on use of dual luciferase reporter assays to measure RBP regulatory function (52).…”
Section: Integrationmentioning
confidence: 99%